Congenital diaphragmatic hernia: New evidence and current and future therapeutic options - Juliani, Alisson; Velho, Giovanna Costa Moura; Vieira, Fernanda Rabelo; Silva, Larissa da (Seven Editora, 2024)
Objectives: To compile the information available in the medical literature and to present the new forms of intervention possible for fetuses and neonates affected by congenital diaphragmatic hernia (CDH). Methodology: a non-systematic literature review of the medical literature was carried out, using the LILACS, SciELO and PubMed databases, with no established period, prioritizing higher levels of scientific evidence. Results: CDH consists of a defect in the embryological closure of the diaphragm, resulting in protrusion of abdominal contents into the thorax. Although rare, CDH imposes significant restrictions on fetal lung development, causing high mortality rates of up to 83%. Its pathogenesis has not yet been fully elucidated, especially at the molecular level, which hinders specific therapeutic approaches. It can occur alone or in association with other congenital malformations. Most cases are diagnosed in the prenatal period by ultrasound, which would make it possible to use early therapeutic techniques to reduce the morbidity caused by the hernia. This type of intervention arouses growing interest among scholars on the subject, seeking methods that can attenuate the severity of pulmonary hypoplasia and pulmonary hypertension, in addition to reducing mortality. Currently, promising results have been observed with endoscopic fetal tracheal occlusion (FETO), a minimally invasive procedure capable of stimulating lung development in fetuses with CDH. However, the most evident change in the approach to the condition was the replacement of emergency surgery in the newborn by clinical stabilization followed by correction of the defect, changing the paradigm of CDH from surgical urgency to "physiological emergency". New therapeutic methods are under development, including attempts to use already known drugs, such as sildenafil and rosiglitazone, with no conclusive results yet. The prognosis varies according to the severity of the diaphragmatic defect and the therapeutic approaches available. Conclusion: numerous studies seek new resources capable of modifying the natural history of CDH. Several techniques have been established, but none has a universal indication. Not even the ideal method of mechanical ventilation of the neonate affected by CDH has been defined in the literature. Therefore, large clinical trials are still needed to determine the best therapeutic options for CDH. DOI:https://doi.org/10.56238/sevened2024.001-042